The Financial Crisis, Austerity Policy And Greece - Eißel, Dieter (Comparative Economic Research. Central and Eastern Europe, 2015)
This article contains a brief review of the main causes of the current crisis and concerns strategies of market dogmatism and their impacts, which followed the end of post-war boom and the end of the so-called Bretton Woods System. Rising inequality and deregulation led to increasing investment of speculative capital (casino capitalism), creating a real estate bubble in USA. Owing to public bailouts, this finance capital did not lose so much after the bubble bursts. However, the bailouts created serious problems for state budgets, which were already poor as a consequence of the tax race to the bottom following the specific neoliberal recommendations to surmount the economic crisis. Together with weak economic performance and high interest rates for state bonds - due low rankings by rating agencies - some states in the euro zone were threatened with insolvency. Additionally, home-made negative structures and mismanagement worsened the situation. The financial assistance then provided by the troika were tied to harsh “reforms” in the spirit of the austerity policy. This has led to a social crisis with colossal humanitarian impacts; it is economically a fiasco and has increased the public debt to unbearable proportions, mainly in Greece, a country which might be seen as a laboratory for this strategy. Central and Eastern European countries could learn by the Greek example of austerity policy: First, they should stay longer to their own currency, allowing them to remain competitive by compensating stronger trade partners’ productivity by the chance of devaluating. Second, it is clear that cutting off expenditures will not solve problems in case of aiming at balancing the public budget. Just the opposite, it will increase social and economic problems by down-sizing public and private demand and it will endanger necessary investments in future development (infrastructure, education). That’s why increasing state receipts and a fair tax policy are on the agenda, as long as the rich escape from contributing adequately to state’s action capability.